An Outdoor Classical Music as an Alternative Media in Teaching English - Anugrah, Agung (La Parole : Journal of Language Teaching and Pedagogy, 2022)
The aims of this research were to obtain the students’ perception and the effect of an outdoor classical music toward the students’ in learning English. Aqualitative method was carried out by researcher in this research. The students’ at Rumah Bambu Pintar were taken as the sample of the research by used total population sampling. The instruments that used in collecting the data were observation, semi-structure interview and documentation. The results of the research shows that an outdoor classical music as alternative media in teaching English could help them in the learning process. There were four participants who suggested that it gave a comfortable impression in learning, and provided a different atmosphere in teaching and learning process. Besides, it also increased the spirit of learning and not easily makes students bored because it was rarely applied in schools.